The modulatory effect of acupuncture on amygdala functional connectivity: narrative review of the clinical research (Research, Society and Development, 2022)
The amygdala is a brain area crucial for emotional, behavioural and visceral sensitivity/motor signals processing. To exert these functions, the amygdala is reciprocally connected with cortical and subcortical regions. Some studies have showed that acupuncture modulates the activity of the amygdala and its circuits. However, there is no literature review synthesizing and evidencing the actual research status about this subject. Thus, the aim of this paper is to present and discuss the newest evidence about the effect of acupuncture on the amygdala resting-state functional connectivity (rsFC) in the context of clinical research. The narrative review of clinical research was focused on published clinical trials (controlled and randomized) designed to analyze the effect of acupuncture on the modulation of the amygdala rsFC in clinical conditions. The search was conducted on Pubmed, ScienceDirect and Scielo databases up to March, 2022. The studies found were about patients with major depressive disorder, functional dyspepsia and premenstrual syndrome, which demonstrated that acupuncture significantly decreases its symptoms. In addition, this therapeutic effect were correlated with the modulation of the amygdala rsFC with a range of brain regions. According to the data reviewed, it can be concluded that the brain action’s mechanisms of acupuncture is related, at least in part for the clinical conditions analyzed, to its modulatory effect on the amygdala network. However, the studies about this theme are rare, and more studies should be done to clarify the amygdala involvement in the effect of the acupuncture.